SUMO chain formation is required for response to replication arrest in S. pombe. - Andrew Skilton; Jenny C Y Ho; Brenda Mercer; Emily Outwin; Felicity Z Watts (PLoS ONE)
SUMO is a ubiquitin-like protein that is post-translationally attached to one or more lysine residues on target proteins. Despite having only 18% sequence identity with ubiquitin, SUMO contains the conserved betabetaalphabetabetaalphabeta fold present in ubiquitin. However, SUMO differs from ubiquitin in having an extended N-terminus. In S. pombe the N-terminus of SUMO/Pmt3 is significantly longer than those of SUMO in S. cerevisiae, human and Drosophila. Here we investigate the role of this N-terminal region. We have used two dimensional gel electrophoresis to demonstrate that S. pombe SUMO/Pmt3 is phosphorylated, and that this occurs on serine residues at the extreme N-terminus of the protein. Mutation of these residues (in pmt3-1) results in a dramatic reduction in both the levels of high Mr SUMO-containing species and of total SUMO/Pmt3, indicating that phosphorylation of SUMO/Pmt3 is required for its stability. Despite the significant reduction in high Mr SUMO-containing species, pmt3-1 cells do not display an aberrant cell morphology or sensitivity to genotoxins or stress. Additionally, we demonstrate that two lysine residues in the N-terminus of S. pombe SUMO/Pmt3 (K14 and K30) can act as acceptor sites for SUMO chain formation in vitro. Inability to form SUMO chains results in aberrant cell and nuclear morphologies, including stretched and fragmented chromatin. SUMO chain mutants are sensitive to the DNA synthesis inhibitor, hydroxyurea (HU), but not to other genotoxins, such as UV, MMS or CPT. This implies a role for SUMO chains in the response to replication arrest in S. pombe.